Modifications of Sarcoplasmic Reticulum Function Prevent Progression of Sarcomere-Linked Hypertrophic Cardiomyopathy Despite a Persistent Increase in Myofilament Calcium Response - Chowdhury, Shamim A. K.; Warren, Chad M.; Simon, Jillian N.; Ryba, David M.; Batra, Ashley; Varga, Peter; Kranias, Evangelia G.; Tardiff, Jil C.; Solaro, R. John; Wolska, Beata M. (Frontiers in Physiology, 2020)
Hypertrophic cardiomyopathy (HCM) is a genetic disorder caused by mutations in different genes mainly encoding myofilament proteins and therefore called a “disease of the sarcomere”. Despite the discovery of sarcomere protein mutations linked to HCM almost 30 years ago, the cellular mechanisms responsible for the development of this disease are not completely understood and likely vary among different mutations. Moreover, despite many efforts to develop effective treatments for HCM, these have largely been unsuccessful, and more studies are needed to better understand the cellular mechanisms of the disease. In experiments reported here, we investigated a mouse model expressing the mutant cTnT-R92Q, which is linked to HCM and induces an increase in myofilament Ca2+ sensitivity and diastolic dysfunction. We found that early correction of the diastolic dysfunction by phospholamban knockout (PLNKO) was able to prevent the development of the HCM phenotype in TnT-R92Q transgenic (TG) mice. Four groups of mice in FVBN background were generated and used for experiments: 1) NTG/PLN, which express wild-type TnT and normal level of PLN; 2) NTG/PLNKO; which express wild-type TnT and no PLN; 3) TG/PLN; which express TnT-R92Q and normal level of PLN; 4) TG/PLNKO; which express TnT-R92Q and no PLN. Cardiac function was determined using both standard echocardiographic parameters and speckle tracking strain measurements. We found that both atrial morphology and diastolic function were altered in TG-PLN mice, but normal in TG-PLNKO mice. Histological analysis showed disarray of myocytes and increased collagen deposition only in TG-PLN hearts. We also observed increased CaMKII phosphorylation only in TG-PLN hearts, but not in TG-PLNKO hearts. The rescue of the HCM phenotype was not associated with differences in myofilament Ca2+ sensitivity between TG-PLN and TG-PLNKO mice. Moreover, compared to standard systolic echo parameters such as ejection fraction (EF), speckle strain measurements provided a more sensitive approach to detect early systolic dysfunction in TG-PLN mice. In summary, our results indicate that targeting diastolic dysfunction through altering Ca2+ fluxes with no change in myofilament response to Ca2+ was able to prevent development of the HCM phenotype and should be considered as a potential additional treatment for HCM patients.